Influence of Whole-Body Electrostimulation on the Deformability of Density-Separated Red Blood Cells in Soccer Players - Filipovic, Andre; Bizjak, Daniel; Tomschi, Fabian; Bloch, Wilhelm; Grau, Marijke (Frontiers in Physiology, 2019)
Red blood cell nitric oxide synthase (RBC-NOS) dependent NO production positively affects RBC deformability which is known to improve oxygen supply to the working tissue. Whole-body electrostimulation (WB-EMS) has been shown to improve maximum strength, sprinting and jumping performance, and to increase deformability in elite soccer players during the season. The aim of the present study was to investigate whether WB-EMS affects RBC turnover which might affect overall deformability of circulating RBC by rejuvenation of the RBC population and if this might be related to improved endurance capacity. Thirty male field soccer players were assigned in either a WB-EMS group (EG, n=10), a training group (TG, n=10) or a control group (CG, n=10). EG performed 3 x 10 squat jumps superimposed with WB-EMS twice per week in concurrent to 2-4 soccer training sessions and one match per week. TG only performed 3 x 10 squat jumps without EMS in addition to their soccer routine and the control group only performed the usual soccer training and match per week. Subjects were tested before (Baseline) and in week 7 (wk-7), with blood sampling before (Pre), 15-30min after (Post) and 24h after (24h post) the training. Endurance capacity was determined before and directly after the training period. The key findings of the investigation indicate an increase in young RBC in the EG group along with improved overall RBC deformability, represented by decreased SS1/2:EImax Ratio. Analysis of the different RBC subfractions revealed improved RBC deformability of old RBC during study period. This improvement was not only observed in the EG but also in TG and CG. Changes in RBC deformability were not associated to altered RBC-NOS/NO signalling pathway. Endurance capacity remained unchanged during study period. In summary, the effect of WB-EMS on RBC physiology seems to be rather low and results are only in part comparable to previous findings. According to the lower training volume of the present study it can be speculated that the soccer specific training load in addition to the WB-EMS was too low to induce changes in RBC physiology.